Pengaruh Profitabilitas, Likuiditas, dan Efisiensi Biaya Operasional terhadap Beban Pajak Penghasilan (PPH) Analisis Perusahaan Industri Dasar dan Kimia di Bursa Efek Indonesia (BEI) - Wisca Nabila Huda; Era Sonita (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research occurs because it is motivated by differences in theory with what happens in the field. As in the Tjiwi Kimia Paper Factory Tbk company and PT Semen Baturaja Tbk company where the profitability value is not in line with the increase in corporate income tax on the company. And at the company PT Unggul Indah Cahya Tbk and PT Ekadharma Internasional Tbk, the large liquidity of the company does not make the corporate income tax on the company increase. As well as in the companies PT Madusari Murni Indah Tbk and PT Sinergi Inti Plastindo Tbk where efficiency in managing operating costs is not in line with the company’s corporate income tax. With the intention of this study aims to see how the relationship of profitability, liquidity and operational cost efficiency to corporate income tax on the company, where corporate income tax is an obligation of the Agency to the government. The research method used in this research is quantitative research. Data is collected by the documentation study method from the company’s financial statements. The type of data used is Secondary Data. Data sourced from audited financial statements published by the company, publicly available capital market data, and additional relevant information from the company’s annual report and IDX database. The results showed that profitability has a positive effect on corporate income tax with a tcount> ttable value of 3.408> 2.028. While liquidity has no effect on corporate income tax with a tcount value < ttable, namely -3,433 < 2,028. Operating cost efficiency has no effect on corporate income tax with a tcount value < ttable, namely -1.810 < 2.028. And simultaneously profitability, liquidity and operational cost efficiency have a simultaneous effect on corporate income tax as evidenced by the value of Fhitung> Ftabel = 17,952> 2,866.